2002
DOI: 10.1381/096089202762252361
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Lap-Band System® up to 7 Years

Abstract: The Lap-band System is an effective procedure for achieving appreciable and stable weight loss at up to 7 years of follow-up (median 36 months). The minimally invasive approach was associated with a short hospital stay and a low rate of complications. Preoperative patient selection, detailed information and availability of the multidisciplinary team permitted us to achieve good longstanding results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(29 citation statements)
references
References 4 publications
4
25
0
Order By: Relevance
“…In general, failure rates after LAGB reach 40% at 5 years [9,11,13,17,22,23]. In the present study, LAGB failure was 30% after a 5-year follow-up.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In general, failure rates after LAGB reach 40% at 5 years [9,11,13,17,22,23]. In the present study, LAGB failure was 30% after a 5-year follow-up.…”
Section: Discussionsupporting
confidence: 52%
“…These results are not easily comparable with this study, since Suter and Martikainen did not use the pars flaccida technique. In general, this technique renders superior results as compared to retrogastric dissection [5,6,7,10,11,13,16,17,18,22,23]. In this study, we experienced more pouch dilatations in patients after a retrogastric band placement (40%) as compared to the pars flaccida technique (4.7%).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This has probably played a crucial role why many bariatric surgeons, meanwhile, prefer the pars flaccida technique. The latter approach has been shown to be associated with a significant lower slippage rate [23][24][25]. In addition, Suter et al reported that differences in slippage rates might also be caused by design differences between the Lap-Band and SAGB devices [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, complications associated with gastric banding are generally minor compared with those seen with other more aggressive weight-loss procedures. While the majority of patients achieve good outcomes with the LAP-BAND, there is a subgroup of patients that experience complications or fail to lose sufficient weight after the banding procedure [2,5,9,18,21,25]. For these patients, we offer a laparoscopic single-step revision from the LAP-BAND System to RYGBP.…”
mentioning
confidence: 99%